Studying the Rate and Causes of Discharge Against Medical Advice in Hospitals Affiliated to Mazandaran University of Medical Sciences - Karimi, Shirzad Asadollah Pour (AVICENA, d.o.o., Sarajevo, 2014)
INTRODUCTION: Discharge against medical advice from the hospital is an important issue from point of view of treatment management, health costs as well as the side effects of treatment stop on patients and their accompanying. Therefore, health managers and planners should consider the predisposing factors that change patient’s mind in this regard. Since, there has been no study to carefully assess the rate and causes of self-discharge in this province, so this study is aimed to fill this gap. METHODS AND MATERIALS: This descriptive and cross-sectional study was carried out in 6 months period, from 23 July 2010 till 20 January 2011 in all public hospitals of Mazandaran province. A form was set out for data collection and those patients willing to self-discharge were asked to participate in the study. Patients’ demographic information was filled using their medical record and by the help of department personnel. Furthermore, the form was completed by parents for patients over 18 year-old or by the help of first-rank relative for those having psychiatric disorders or anybody who wasn’t able to complete the form. In order to identify the causes of self-discharge, 18 variables were determined which were categorized in three general items and five main groups. Data were entered into the SPSS15 and were analyzed using descriptive statistics indices. RESULTS: According to the results, 94441 were discharged from the university hospitals which 7967 patients (8.4 %) of them were self-discharged during the 6 month study period. Regarding admission type, 269 (3.3 %), (54.5 %) were admitted into the hospital by pre-determined appointment and as usual patients, respectively, and the rest were admitted by emergency department. Also, 31.4%(2504) were hospitalized in surgery ward, 63% (5026) in medical ward, 4.6% (374) in intensive care unit (ICU) and the rest were hospitalized in the psychiatric ward. The most important reasons for self-discharge were related to: 1-factors affecting patient illness (54.3%), 2-environmental issues as well as patients’ accompanying (37.6%) and 3-managerial and medical reasons(7.9%), respectively. CONCLUSION: Our study showed the same results for Discharge against medical advice rate as the others. From the view point of treatment management, its causes should be considered and practices should be done to improve the conditions. Meanwhile, the current self-discharge form doesn’t reflect the causes of the problem and it should be revised.